Investigation of LD50, GR50 and seedling development in sodium azide and ethyl methane sulfonate treatments of chickpea (Cicer Arietinum L.) - Tarhan, Mehmet; Bicer, Behiye Tuba (Bangladesh Journal of Botany, 2025)
The effects of different doses of sodium azide (SA) and ethyl methane sulfonate (EMS) on seedling and root characteristics of chickpea variety were investigated. Lethal dose (LD50) and median growth reduction (GR50) values were determined for mutagens. In EMS treatment, Lethal dose was 47.4 mM and median growth reduction was 12.5 mM. Mutation efficiency was not determined at SA doses and it was revealed that higher doses would create mutants. As SA and EMS doses increased, the number of days to germination increased and seedling and root development decreased. Seeds germinated at 40 and 50mM EMS doses but seedlings did not survive. Differences between low and high doses in SA treatments were low. Leaf and plant mutants had 60% mutation efficiency at 20mM dose of EMS. Bangladesh J. Bot. 54(3): 419-424, 2025 (September)